Sphingosine 1-Phosphate Receptor 4 Expression in Colorectal Cancer Patients - SAMUHASANEETO, Suchittra; PROMAGSORN, Suthiporn; PUNSAWAD, Chuchard (Walailak Journal of Science and Technology (WJST), 2016)
The aim of this study was to investigate the expression of S1PR4 in colorectal cancer and its correlation with clinicopathologic characteristics. Paraffin-embedded colorectal cancer samples and matched adjacent normal tissues were collected from 32 patients at Maharat Nakhon Si Thammarat Hospital. The expression of SphK1 and S1PR4 in colorectal cancer and matched normal tissues were determined by immunohistochemistry and compared with the clinicopathologic characteristics for each of the 32 colorectal cancer patients. There were 20 males (62.50 %) and 12 (37.50 %) females. The mean age was 59.66±12.66 years. The majority of tumors were moderately differentiated (62.50 %). A high level of SphK1 and S1PR4 protein expression was observed in tumor samples compared with adjacent normal mucosa (P = 0.005 and P = 0.02, respectively). The neoplastic cells showed positive cytoplasmic staining expression for both SphK1 and S1PR4 proteins. The distribution of these 2 proteins in colorectal cancer patients showed that neither were significantly correlated to clinicopathologic features such as sex, age, pathological stage, T stage, N stage, M stage, tumor differentiation, tumor location or tumor size. It was found that S1PR4 was overexpressed in colorectal cancer and may influence tumor progression, however, there was no correlation between S1PR4 expression and clinicopathologic characteristics.